PERANTARA KINERJA LINGKUNGAN YANG BAIK DALAM AKUNTANSI HIJAU MENDORONG KINERJA KEUANGAN - Langgeng Prayitno Utomo (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2022)
When green accounting is combined with environmental costs, it shows that businesses who want to make more money will take into consideration all expenses, even those that have a negative impact on the environment. The purpose of this study is to ascertain how green accounting affects financial performance in main consumer goods manufacturing companies listed on the Indonesia Stock Exchange for the years 2021–2023, using environmental performance as a mediating variable. The study used a quantitative technique and purposive selection to select samples from 108 data sets that were taken from each company's sustainability and annual reports. Path analysis was the data analysis method employed. The findings show that financial performance is positively impacted by green accounting, environmental performance is positively impacted by green accounting, and the relationship between green accounting and financial performance is mediated by environmental performance.